Фізіолого-біохімічні методи стимулювання проростання насіння шипшин - Tkachuk, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The methods and results of researches of stimulation of dog roses seeds germination before sowing are adduced.